Clinical Outcomes of Extreme Lateral Interbody Fusion in the Treatment of Adult Degenerative Scoliosis. (24th September 2012) - Caputo, Adam M.; Michael, Keith W.; Chapman, Todd M.; Massey, Gene M.; Howes, Cameron R.; Isaacs, Robert E.; Brown, Christopher R.
Abstract : Introduction . The use of extreme lateral interbody fusion (XLIF) and other lateral access surgery is rapidly increasing in popularity. However, limited data is available regarding its use in scoliosis surgery. The objective of this study was to evaluate the clinical outcomes of adults with degenerative lumbar scoliosis treated with XLIF. Methods . Thirty consecutive patients with adult degenerative scoliosis treated by a single surgeon at a major academic institution were followed for an average of 14.3 months. Interbody fusion was completed using the XLIF technique with supplemental posterior instrumentation. Validated clinical outcome scores were obtained on patients preoperatively and at most recent follow-up. Complications were recorded. Results . The study group demonstrated improvement in multiple clinical outcome scores. Oswestry Disability Index scores improved from 24.8 to 19.0 ( P < 0.001). Short Form-12 scores improved, although the change was not significant. Visual analog scores for back pain decreased from 6.8 to 4.6 ( P < 0.001) while scores for leg pain decreased from 5.4 to 2.8 ( P < 0.001). A total of six minor complications (20%) were recorded, and two patients (6.7%) required additional surgery. Conclusions . Based on the significant improvement in validated clinical outcome scores, XLIF is effective in the treatment of adult degenerative scoliosis.